Peran Integratif Keluarga Dan Kader Posyandu Dalam Edukasi Gizi Sebagai Upaya Pencegahan Stunting Pada Ibu Hamil Di Desa Semen - Hidayah, Nurul; Marwan, Marwan; Martojo, Bambang R.E (Rahmah : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to identify the integrative role of families and Posyandu cadres in nutrition education as an effort to prevent stunting in pregnant women in Semen Village. This community service method applies a nutrition education intervention with a participatory approach in Semen Village in 2025. The activity involved 35 pregnant women, 35 accompanying family members (husbands or grandmothers), and 35 Posyandu cadres. The results of the activity showed that pregnant women's nutritional knowledge increased significantly from 56.14 to 82.37 (p < 0.001). Family support for animal protein consumption increased from 35.3% to 80%, while father involvement in pregnancy check-ups increased from 20.5% to 65.2%. Posyandu cadres' knowledge also increased from 60.21 to 85.07 (p < 0.001). The nutrition education approach with the integrative role of families and Posyandu cadres has proven effective in increasing nutritional literacy, family support, and cadre capacity in preventing stunting.